Aspek Sosial dalam Kumpulan Cerita Anak Ulin di Monumen Karya Tetty Hodijah - Sari, Kurnia (LOKABASA, 2019)
This research is motivated by the lack of awareness of the community to appreciate literary works that contain many social values. This study aims to describe the social aspects contained in the collection of Ulin children's stories at Monumén by Hodijah Tetti. The method used in this study is a descriptive analysis method, using steps to collect data from a collection of children Ulin in Monumén, analyze the data collected, and describe the data. The main data source of this research is the book collection of Ulin's short stories in Monumén by Tetti Hodijah. The data obtained is in the form of notes on the results of a literature study. The results of this study found 3 social aspects, namely social aspects of religion, socio-economic aspects, and social aspects of education. From the social aspect of religion, 3 elements related to religion were found, namely believing in Allah SWT, carrying out the commands of Allah SWT, and being sincere and thankful to Allah SWT. From the socio-economic aspect, it was found 3 levels of economy, namely the upper class economy, and middle class economy. From the socio-educational aspect, six elements of education were found, namely manners, mutual respect, love for the country, far from being jealous and envious, and learning to obey the rules that apply in society.